Inhibitory effect of topical antibiotics/antiseptics administration on bacterial growth in the open wound of the jawbone surgery: Randomized controlled, preliminary study - Souichi Yanamoto; Sakiko Soutome; Shoma Tsuda; Kota Morishita; Saki Hayashida; Saori Harata; Maho Murata; Keisuke Omori; Satoshi Rokutanda; Masahiro Umeda (Elsevier, 2021)
Background/purpose: TThe bone cavities after extirpation of cysts or tumor of the jawbone requires the insertion of gauze containing various antibiotics/antiseptics to minimize the risk of pain, bleeding, and surgical site infection (SSI). However, there have been few reports on the efficacy of topical administration of antibiotics/antiseptics to an open wound of the jawbone. To compare the inhibitory effects of topical povidone-iodine gel and tetracycline ointment on the jawbone wound bacterial growth after extirpation of cyst or tumor. Materials and methods: This is a preliminary, randomized controlled, open-labeled trial. Eighteen patients were randomly assigned into two groups. In povidone-iodine (PI) group, gauze mixed with povidone-iodine gel was inserted into the bone cavity wound, and in tetracycline (TC) group gauze mixed with tetracycline ointment was inserted after extirpation of cyst or tumor of the jaw bone. In both groups, gauze was removed 48 h after surgery, and examined by bacterial culture and real-time polymerase chain reaction (PCR) using primers detecting total bacteria and MRSA. Results: The topical application of tetracycline ointment was superior to that of povidone-iodine gel concerning inhibitory effects of total bacteria and methicillin-resistant Staphylococcus aureus (MRSA). Conclusion: This preliminary study suggests that the insertion of gauze mixed with tetracycline ointment is recommended for bone wounds after extirpation of cyst or tumor of the oral cavity.